A contribuição da Maçonaria para a prática educativa em Aracaju (1970-1980) - Nascimento, José Anderson (2010)
The object of this work is to present to the academic community the contribution of the Masonry, in special of the Store Maçônica Cotinguiba, for practical the educational one in Aracaju. For the achievement of this desideratum, we develop a research with a necessary object, using it notion of the social elites to assign maçons, therefore they had formed the elite politics, enterprise, administrative and military of Brazil. As secular landmark we fix the decade of 1970, when Liga Sergipense Against the Illiteracy, civil association tied with the Store Maçônica Cotinguiba, offered a course of typewriting with the purpose to prepare hand of workmanship specialized for commercial companies, banks and lenders of services, in Aracaju. The beddings of the research are seated in Cultural History, therefore Verbal History is proven, in the sedimentation of the work. For the construction of the theoretical referencial we appeal to the teachings of Jaques Le Goff, Paul Veyne, Roger Chartier, Pierre Nora, Verena Alberti and Alexis Tocqueville. Established the object, general objective and referencial theoretician, we detach the problem of the research, that consists of knowing as the sergipana Masonry it influenced practises it of professionalizing education in Aracaju. We use the methodology of the bibliographical research, beyond documents and interviews under whose information we structuralize the text in two chapters: in the first one one studies the origins of the Masonry and the Masonry in Brazil and, in as it deals with the Masonry in Sergipe and its contribution for professionalizing education in Aracaju.